Analisis Jejaring Kebijakan dalam Program Sertifikasi Permukiman di Atas Air di Kelurahan Kawal Kecamatan Gunung Kijang Kabupaten Bintan - Ayunatasya; Safitri, Dian Prima; Firman, Firman (Pencerah, 2024)
The certification program for settlements on the water is carried out as a form of ensuring legal protection for community settlements on the water. So far, it has been difficult for the community to get a certificate because they are above the sea, not on land like people who generally live on land. The purpose of this research is to find out and describe the policy networks involved in the implementation of the overwater settlement certification program in Kawal Village, Gunung Kijang District, Bintan Regency. The theory used is Van Waarden's theory (1992) with indicators of actors, functions, structures, institutions, rules of action, power relations, and actor strategies. The results of this study show that the policy network involved in the implementation of the overwater settlement certification program consists of the Central Government, Provincial Government, District Government, and Village Government. The mechanism for implementing the overwater settlement certification program in Bintan Regency, especially in Kawal Village, is based on the Decree of the Director General of Marine Spatial Management Number 15 of 2023 concerning Guidelines for Facilitating Approval of Conformity of Marine Spatial Utilization Activities for Local Communities in Coastal Areas and Small Islands. The implementation of this program certainly has obstacles in the field, namely related to coordination between agencies, especially at the regional level, on the implementation of socialization, facilities and access when going to the field. Researchers suggest the need to empower policy networks outside the government and the private sector.